x(x-3)-4x+12=0
<=> x(x-3)-4(x-3)=0
<=> (x-3)(x-4)=0
<=> x-3=0 <=>x=3
x-4=0 <=>x=4
Vậy phương trình có tập nghiệm là S = 3;4
\(x\left(x-3\right)-4x+12=0\)
\(\Leftrightarrow x^2-3x-4x+12=0\)
\(\)\(\Leftrightarrow\left(x^2-3x\right)-\left(4x-12\right)=0\)
\(\)\(\Leftrightarrow x\left(x-3\right)-4\left(x-3\right)=0\)
\(\Leftrightarrow\left(x-3\right)\left(x-4\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x-3=0\\x-4=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=3\\x=4\end{matrix}\right.\)
Vậy phương trình có nghiệm x = 3 hoặc x = 4 .